PAD4 Inhibitor‐Functionalized Layered Double Hydroxide Nanosheets for Synergistic Sonodynamic Therapy/Immunotherapy Of Tumor Metastasis - Di Zhu; Yu Lu; Shuqing Yang; Tingting Hu; Chaoliang Tan; Ruizheng Liang; Yuji Wang (Advanced Science, 2024)
Abstract Sonodynamic therapy (SDT) is demonstrated to trigger the systemic immune response of the organism and facilitate the treatment of metastatic tumors. However, SDT‐mediated neutrophil extracellular traps (NETs) formation can promote tumor cell spread, thus weakening the therapeutic effectiveness of metastatic tumors. Herein, the amorphous CoW‐layered double hydroxide (a‐CoW‐LDH) nanosheets are functionalized with a peptidyl arginine deiminase 4 (PAD4) inhibitor, i.e., YW3‐56, to construct a multifunctional nanoagent (a‐LDH@356) for synergistic SDT/immunotherapy. Specifically, a‐CoW‐LDH nanosheets can act as a sonosensitizer to generate abundant reactive oxygen species (ROS) under US irradiation. After loading with YW3‐56, a‐LDH@356 plus US irradiation not only effectively induces ROS generation and immunogenic cell death, but also inhibits the elevation of citrullinated histone H3 (H3cit) and the release of NETs, enabling a synergistic enhancement of anti‐tumor metastasis effect. Using 4T1 tumor model, it is demonstrated that combining a‐CoW‐LDH with YW3‐56 stimulates an anti‐tumor response by upregulating the proportion of immune‐activated cells and inducing polarization of M1 macrophages, and inhibits immune escape by downregulating the expression of PD‐1 on immune cells under US irradiation, which not only arrests primary tumor progression with a tumor inhibition rate of 69.5% but also prevents tumor metastasis with the least number of lung metastatic nodules.